Heterogeneous production constraints and postharvest losses in onion farming: evidence from Northwest Ethiopia - Yeshiwas, Yebirzaf; Tadele, Esubalew; Adgo, Enyew; Alemayehu, Melkamu (Frontiers in Sustainability, 2025)
IntroductionOnion (Allium cepa L.) production in Ethiopia is highly seasonal, while consumption remains year-round, creating critical mismatches between supply and demand. The crop’s perishability and limited storage capacity force farmers to sell quickly at low prices, driving market gluts and substantial postharvest losses. This study examines the determinants of onion production and postharvest losses along the supply chain in northwestern Ethiopia.MethodsA multi-stage sampling strategy covered three districts (Fogera, North Mecha, and Bahir Dar Zuria) and six kebeles, yielding data from 167 producers, 30 wholesalers, 50 retailers, and 50 consumers, complemented by key informant interviews and field observations.Results and discussionMultiple linear regression models, validated for multicollinearity (VIF < 10) and heteroscedasticity (Breusch–Pagan test), revealed that male household headship (β = 1.561, p < 0.05), hybrid seed access (β = 4.40, p < 0.05), and land allocation (β = 16.49, p < 0.01) significantly increased production (R2 = 0.901). Conversely, education (β = −0.51 to −0.31, p < 0.1) and cooperative membership (β = −0.906, p < 0.1) reduced postharvest losses, whereas land size (β = 4.30, p < 0.01), future price expectations (β = 2.17–4.20, p < 0.1), and purchase volume (β = 1.55–4.43, p < 0.01 at wholesale) amplified them. These results highlight persistent gender disparities, input access gaps, and systemic storage constraints. Policy priorities include scaling hybrid varieties, upgrading storage technologies, strengthening cooperatives, and providing targeted capacity building and enhancing supply chain efficiency. Strengthening these areas will be pivotal for advancing sustainable food security and rural income resilience.